Aplicação da sistemática Shop Floor Management nas atividades de validação de itens novos de uma fabricante de carrocerias de ônibus - Araújo, Fernando Constante de (Universidade do Vale do Rio dos Sinos, 2025)
The competitive dimension of quality remains one of the main requirements of the market, where companies have certified their processes and structured areas dedicated to carrying out inspection and quality control activities. Management systems such as Lean Manufacturing are now being adopted by companies to improve quality, reduce lead time and reduce costs. In this scenario, the action research method presents the opportunity to implement a visual management model based on Lean Manufacturing practices in quality activities. The management model defined was Shop Floor Management (SFM), its main characteristic is holistic management, which in turn aims to solve problems and develop the people involved in the process, by presenting the results through KPIs and correcting problems and daily corrections regarding issues of occupational safety, quality, delivery, costs and people's motivation, thus systematizing the continuous improvement of processes and products. The research is applied to the activities of the validation processes of new items in the quality sector of a bus body manufacturer, and the effects on the indicators of the delivery dimension are observed, referring to the average time for validation of new items, approval of new items, average time for warranty of items from suppliers and the accuracy index of the warehouses under the responsibility of quality. A comparison of the before and after results in the delivery issues, as well as the scope in the motivational issues of those involved is also presented, validating the concept of a holistic mechanism for the daily management of factory floor activities.
Keywords: Gerenciamento visual; Shop Floor Management; Qualidade; Lean Manufacturing; Gestão Lean; Visual management; Quality; Lean Management; ACCNPQ::Engenharias::Engenharia de Produção